Epidemiology of constipation and its associated factors in an ageing population of people with an intellectual disability in Ireland: A cross-sectional study. - Burke, Eilish; Mc Carron, Mary (My University, 2024)
Background: Constipation impacts health-related quality of life with a burden similar to other chronic conditions. This study characterises the prevalence of constipation and its associated factors in older adults with intellectual disability. Methods: Data from the Intellectual Disability Supplement of The Irish Longitudinal Study on Ageing was analysed using bivariate and multivariate approaches. Results: Constipation affected 43.5% of this cohort and was more common in females, those in residential settings, and those with a severe/profound level of intellectual disability. The type of residence, level of intellectual disability, a low fat diet, high cholesterol, multimorbidity and, physical activity predicted constipation status with 67.7% accuracy. Physical activity was associated with lower constipation prevalence, where minimal activity was sufficient to observe this effect. Conclusions: Constipation is a common health concern in older people with intellectual disability. This analysis reveals characteristics that should inform the careful monitoring of bowel health in this population.
PUBLISHED
Keywords: Diet; Constipation; Intellectual disability; Older people; Multimorbidity; Physical activity; Ageing; Ageing & Intellectual Disability - Changing Service Needs; Ageing & Intellectual Disability Issues; Ageing, Health and Intellectual Disability; CHRONIC CONSTIPATION; Intellectual Disability Nursing; Chronic Health Condition; Intellectual Disability; Health